2015
DOI: 10.1124/jpet.115.230839
|View full text |Cite
|
Sign up to set email alerts
|

Diisopropylfluorophosphate Impairs the Transport of Membrane-Bound Organelles in Rat Cortical Axons

Abstract: The extensive use of organophosphates (OPs) is an ongoing environmental health concern due to multiple reports of OPrelated neurologic abnormalities. The mechanism of the acute toxicity of OPs has been attributed to inhibition of acetylcholinesterase (AChE), but there is growing evidence that this may not account for all the long-term neurotoxic effects of OPs. In previous experiments (using ex vivo and in vitro model systems) we observed that the insecticide OP chlorpyrifos impaired the movements of vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…Mitochondria are the primary site of energy production and have been suggested to be the target of noncholinergic toxicity of OPs . Past studies have indicated a link between exposure to higher concentrations of OP and oxidative stress and transport deficits after OP exposure . Consistent with previous work, when neurons were treated with the DFP, transport of mitochondria was impaired and mitochondrial length increased, suggesting an increase in mitochondrial fusion.…”
Section: Resultssupporting
confidence: 70%
“…Mitochondria are the primary site of energy production and have been suggested to be the target of noncholinergic toxicity of OPs . Past studies have indicated a link between exposure to higher concentrations of OP and oxidative stress and transport deficits after OP exposure . Consistent with previous work, when neurons were treated with the DFP, transport of mitochondria was impaired and mitochondrial length increased, suggesting an increase in mitochondrial fusion.…”
Section: Resultssupporting
confidence: 70%
“…Since there was no reliable literature data on the stability of DFP in DMSO or in aqueous buffers used for tissue culture or imaging experiments, we also investigated the stability of DFP in solution and the rate at which it hydrolyses into diisopropyl phosphoric acid through nucleophilic substitution of the F. This hydrolysis can be easily monitored by the diminishing octet at 4.77 ppm and the appearance of a shifted octet at 4.51 ppm in the 800‐Hz 1 H‐NMR spectrum or the change of the 31 P signal from a doublet induced by the coupling to the F in DFP to a singlet in the hydrolysis product that no longer contains F. While DFP was highly stable in DMSO and showed no signs of hydrolysis even after 19 days, it hydrolyzed quickly in unbuffered deionized water, which is typically acidic. DFP was reasonably stable in phosphate‐buffered solutions, where it showed no signs of hydrolysis over 20 h, suggesting that it would be sufficiently stable in tissue culture experiments or imaging experiments that last less than 24 hours . Therefore, we believe that DFP is stable in the Ca 2+ ‐imaging experiments described above.…”
Section: Challenges Associated With Model Developmentmentioning
confidence: 86%
“…DFP was reasonably stable in phosphate-buffered solutions, where it showed no signs of hydrolysis over 20 h, suggesting that it would be sufficiently stable in tissue culture experiments or imaging experiments that last less than 24 hours. 54 Therefore, we believe that DFP is stable in the Ca 2+ -imaging experiments described above.…”
Section: Challenges Associated With Model Developmentmentioning
confidence: 89%
“…CPF-induced impairments in axonal transport can partially be explained by altered motility of mitochondria and changes in motor proteins like kinesin and microtubules, as well as motor-associated proteins like tubulin (Gearhart et al, 2007; Prendergast et al, 2007; Grigoryan and Lockridge, 2009; Middlemore-Risher et al, 2011). Similar impairments in motor proteins are induced by DFP exposure, which may also impair axonal transport (Gearhart et al, 2007; Gao et al, 2016). …”
Section: Mechanisms Of Chronic Op Neurotoxicitymentioning
confidence: 87%